Perceived neighborhood ethnic diversity and social outcomes: Context-dependent effects within a postindustrial city undergoing regeneration - Kearns, Ade (2018)
This article examines whether perceived neighborhood ethnic diversity is associated with a range of social outcomes in a postindustrial city undergoing regeneration. The research included a survey in 3 types of deprived area in Glasgow: those undergoing regeneration, those directly adjoining regeneration areas, and those further removed from regeneration areas. In areas undergoing regeneration, perceived diversity was positively associated with many residential, cohesion, safety, and empowerment outcomes. This was also true, although to a lesser extent, in deprived areas at some distance from regeneration areas. In areas immediately surrounding the regeneration areas, perceived diversity had mixed associations with residential and safety outcomes and few associations with cohesion and empowerment outcomes. The results suggest that the effects of perceived diversity are context dependent within a city. Moreover, regeneration processes alter neighborhood contexts and therefore enable scale, timing, and duration of diversity to mediate the relationships between perceived diversity and social outcomes